Model Pengendalian Stunting bagi Balita Usia 0-24 Bulan di Desa Kapur Kecamatan Sungai Raya Kabupaten Kubu Raya: Stunting Control Model for Toddlers Age 0-24 Months in Kapur Village, Sungai Raya District, Kubu Raya Regency - Desi Desi; Martunis Ginting; Yanuarti Petrika (Jurnal Surya Medika (JSM), 2022)
Stunting in children reflects the failure to thrive in children under five. so the child becomes too short for his age. This is due to chronic malnutrition that occurs from the womb until age two. Empowerment of cadres is a strategy used to increase the ability and realize the independence of cadres in carrying out their roles and functions in the development of public health. This study aims to determine the effect of empowering posyandu cadres in detecting stunting for toddlers aged 0-24 months in Desa Kapur, Sungai Raya District, Kubu Raya Regency. The research design used was experimental research using a one-group pre-test and post-test approach. Before the treatment was given a pretest (initial test) and, at the end, was given a posttest (final test). the number of samples as many as 35 people. Data were taken using questionnaires and observation sheets. The results of this study indicate that there is an effect of training in measuring body length using a length board on the skills of cadres in taking measurements for toddlers aged 0-24 months with a significant value (p = 0.000). There is an increase in the ability of cadres to detect stunting after training in measuring body length using a length board from 0% to 100%. Body length measurement training for Posyandu cadres is a form of Empowering Posyandu Cadres in Stunting Control Models at 1000 HPK in Desa Kapur, Sungai Raya District, Kubu Raya Regency.